2021
DOI: 10.3390/su13052599
|View full text |Cite
|
Sign up to set email alerts
|

Transforming a Valuable Bioresource to Biochar, Its Environmental Importance, and Potential Applications in Boosting Circular Bioeconomy While Promoting Sustainable Agriculture

Abstract: Biochar produced from transforming bioresource waste can benefit sustainable agriculture and support circular bioeconomy. The objective of this study was to evaluate the effect of the application of biochar, produced from wheat straws, and a nitrification inhibitor, sourced from neem (Azadirachta indica), in combinition with the recommended synthetic fertilizer on soil properties, maize (Zea mays L.) plant growth characteristics, and maize grain yield and quality paramters. The nitrification inhibitor was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 85 publications
1
2
0
Order By: Relevance
“…This increase in yield is found to be statistically significant. These findings also stand indicated by the study findings of 17 , 18 , 28 , 31 , who found that application of NCU following the site-specific nutrient management principles had led to crop production of higher or similar levels as observed with untreated urea, but with lower fertilizer application rates.…”
Section: Resultssupporting
confidence: 64%
“…This increase in yield is found to be statistically significant. These findings also stand indicated by the study findings of 17 , 18 , 28 , 31 , who found that application of NCU following the site-specific nutrient management principles had led to crop production of higher or similar levels as observed with untreated urea, but with lower fertilizer application rates.…”
Section: Resultssupporting
confidence: 64%
“…Instead, biochar produced from wheat-straw along with specific nitrification-inhibitor sourced from neem plants with the recommended dose of synthetic fertilizer could significantly improve soil nutrition for good maize crops. This highlights the vital importance of agriculture waste as a valuable resource in the circular bioeconomy [22] .…”
Section: Introductionmentioning
confidence: 93%
“…Pengelolaan sampah yang tepat dapat membantu mencapai manfaat ekonomi yang lebih besar sekaligus melindungi lingkungan dan kesehatan manusia1. Manfaat lingkungan: Mengubah sampah dapat memberikan manfaat bagi lingkungan, seperti mengurangi polusi dan emisi gas rumah kaca (Abbas et al, 2021). Sebagai contoh, biochar yang dihasilkan dari mengubah limbah bioresources dapat bermanfaat bagi pertanian berkelanjutan dan mendukung bioekonomi sirkular (Abbas et al, 2021).…”
Section: Pendahuluanunclassified
“…Manfaat lingkungan: Mengubah sampah dapat memberikan manfaat bagi lingkungan, seperti mengurangi polusi dan emisi gas rumah kaca (Abbas et al, 2021). Sebagai contoh, biochar yang dihasilkan dari mengubah limbah bioresources dapat bermanfaat bagi pertanian berkelanjutan dan mendukung bioekonomi sirkular (Abbas et al, 2021). Pembangunan berkelanjutan: Pengelolaan sampah yang tepat sangat penting bagi gagasan pembangunan berkelanjutan dan dapat membantu melindungi lingkungan dan kesehatan manusia (Szyba & Muweis, 2022).…”
Section: Pendahuluanunclassified